Understanding room-temperature magnetic properties of anthropogenic ashes from municipal solid waste incineration to assess potential impacts and resources. (20th July 2020) - Funari, V.; Mantovani, L.; Vigliotti, L.; Dinelli, E.; Tribaudino, M.
Abstract: Environmental magnetic studies are widely used to trace sources of anthropogenic pollution and have revealed promising applications to the urban waste management system. Here, a collection of solid samples from Municipal Solid Waste Incinerators (MSWI) were studied to probe the capability of geochemical and magnetic data integration as a tool for assessing mineralogy, grain-size, and metal enrichment. A data set of room-temperature magnetic parameters was compared with chemical data by X-ray fluorescence and electron microscopy observations. The aim was to validate or reject methods for urban mining purposes, testing and exploiting the correlations that magnetic properties typically experience with iron and heavy metals, as well as their relation to magnetic grain-sizes (from mm-scale down below 30 nm). We noted that the room-temperature magnetic data of MSWI ashes, used to assess grain-size according to the magnetic domain states, is complicated by the clumping of tiny and large grains displaying similar magnetic properties, so it needs to be supported by optical methods or more advanced magnetic techniques. On the other hand, the integration between magnetic and geochemical data, constrained by the analyses of the magnetic/diamagnetic extracts, helped in assessing magnetic mineral assemblages and potential metal enrichment. Highlights: A way for the practical use of room-temperature magnetic properties in waste management is proposed. Integrating magnetic properties to geochemical/mineralogical data helped for a better, rapid assessment of iron phases. Magnetic domain states assessed by magnetic techniques remain controversial for grain-size evaluation. Multiparametric plots to prospect metals from incineration waste are proposed but need confirmation by new data.